Grassland farmers' relationship with biodiversity: a case study from the northern Italian Alps. Issue 1 (31st December 2022) - Moroder, Alma Maria; Kernecker, Maria Lee
ABSTRACT: To successfully understand and shape biodiversity conservation in Alpine grasslands, it is crucial to understand how farmers' relationship to biodiversity influences their goals and associated practices. We explored how farmers perceive and value biodiversity, how this is related to agricultural and land use practices, and how they view their roles in affecting it. Semi-structured interviews were conducted with 22 farmers in the northern Italian Alps and with 6 experts in the fields of grassland management, agriculture, and environmental conservation in 2020. The farmers' answers were analyzed using a mental model approach, relational thinking, and the literature on the 'good farmer'. The experts' responses were used to discuss and contextualize the farmer's answers. We found that the farmers' mental model of biodiversity is associated to different aspects of agricultural management practices and farmers' roles in mountain agricultural landscapes. Instrumental values of biodiversity are negative and strongly perceived as such by farmers, while relational values associated with biodiversity are positive, but more weakly perceived. These differing perceptions and values seem to be associated with two roles that farmers have, as producers and landscape stewards, and how they value fodder quantity and quality. Most farmers don't include considerations related to the conservation of biodiversity in their management decisions, and mostly do not envision any changes in biodiversity or management in the future. Effective biodiversity conservation in Alpine grasslands will therefore need to tap into these dual roles and the associated instrumental and relational values of biodiversity for a meaningful dialogue on conservation.